PENGARUH KOMITE AUDIT, LAMA PERIKATAN AUDIT DAN AUDIT CAPACITY STRESS TERHADAP KUALITAS AUDIT - Arum Ardianingsih (LPPM Universitas Pekalongan, 2014)
Financial scandals occurred not only in America but also in Indonesia . The impact of the scandal was carried out order conditions and regulatory reform business practices . Sarbanes Oxley Act ( SOX ) make improvements and tightening the audit and its supporting components. Efforts to improve the quality of the audits performed by requiring a minimum level per year, limiting the engagement period ( tenure ) auditors and their clients , as well as establish an audit committee ( Baridwan and Hariani , 2010 ). This study aims to provide empirical evidence of the influence of the audit committee , the audit engagement and long stress audit capacity to audit quality. The research method used logistic regression with sampling techniques using purposive sampling. Data using banking companies listed on the Stock Exchange 2008-2012 period . The results showed that the audit committee ( X1 ) had no significant effect on audit quality ( Y ) with a significance level that is equal to 0,999, the audit engagement length ( X2 ) had no significant effect on audit quality ( Y ) with a significance level that is equal to 0.913 , Audit stress capacity ( X3 ) had no significant effect on audit quality ( Y ) with a significance level that is equal to 0.913. Keywords : quality of the audit, the audit committee, the audit and the audit engagement old stress capacity.